Providing Access to Genomic Variant Knowledge in a Healthcare Setting: A Vision for the ClinGen Electronic Health Records Workgroup. Issue 2 (9th November 2015) - Overby, CL; Heale, B; Aronson, S; Cherry, JM; Dwight, S; Milosavljevic, A; Nelson, T; Niehaus, A; Weaver, MA; Ramos, EM; Williams, MS
Abstract : The Clinical Genome Resource (ClinGen) is a National Institutes of Health (NIH)‐funded collaborative program that brings together a variety of projects designed to provide high‐quality, curated information on clinically relevant genes and variants. ClinGen's EHR (Electronic Health Record) Workgroup aims to ensure that ClinGen is accessible to providers and patients through EHR and related systems. This article describes the current scope of these efforts and progress to date. The ClinGen public portal can be accessed atwww.clinicalgenome.org .